Implications of Telemedicine in Oncology during the COVID-19 Pandemic - Shirke, Manasi Mahesh; Shaikh, Safwan Ahmed; Harky, Amer (Acta Biomedica Atenei Parmensis, 2020)
COVID-19 has had a catastrophic effect on healthcare systems compromising the treatment of cancer patients. It has an increased disease burden in the cancer population. As a result, tele-oncology services have become essential to reduce the risk of cancer patients being exposed to the deadly pathogen. Many governmental establishments have endorsed the use of tele-oncology during COVID-19 era. However, telemedicine in oncology still has certain drawbacks that can be improved upon. Nevertheless, tele-oncology has shown great promise to support cancer care not only during this pandemic but also become a part of normal care in the future.